Photovoltaic and photocatalytic performance of electrospun Zn2SnO4 hollow fibers - Das, P. P.; Roy, A .; Tathavadekar, M.; Devi, P. S. (Applied Catalysis B, 2017)
The phase pure hollow Zn2SnO4 and green emitting ZnO-SnO2-Zn2SnO4 composite fiber have been prepared by post calcining the as formed fiber by electrospin technique. Depending upon the calcination temperature, the as prepared fiber exhibited a striking variation in composition, microstructure, optical and photo-electrochemical properties. The composition dependent dissimilarity in photovoltaic performance and photocatalytic activity has been established in this work. A relatively enhanced open circuit voltage (Voc) of 0.76 V, fill factor (FF) of 59.78%, short circuit current Qsc) of 4.2 mA/cm(2) and an overall conversion efficiency (n) of 1.93% have been achieved for the phase pure Zn2SnO4 porous fiber obtained at the elevated calcination temperature of 1000 degrees C. On the contrary, a relatively reduced Voc, FF, J(sc) and n of 0.70 V, 42.54%, 3.8 mA/cm(2) and 1.17%, respectively, have been achieved for the 800 degrees C calcined dense fiber consisting of a mixture of three distinct phases ZnO, SnO2 and Zn2SnO4. Unlike photovoltaic behaviour the trend in photocatalytic performance interestingly got reversed for the ZnO-nO(2)-Zn2SnO4 composite fiber owing to its superior photo-induced charge separation ability followed by generation of larger amount of active hydroxyl radicals (OFF). Our results establish the composite fiber as a preferred photocatalyst in comparison to phase pure Zn2SnO4 towards the textile dyes Methylene blue and Congo red and non absorbing organic pollutants such as Phenol and Bisphenol A under UV illumination.